Employees’ Viewpoint On Corporate Social Responsibility (Csr) Practices: A Preliminary Study On Universiti Putra Malaysia - Chan , Tak Jie; Mohd Hasan, Nurul Ain; Waheed, Moniza (2015)
In the past few decades, research in Corporate Social Responsibility (CSR) has emerged tremendously in the corporate and academic world. Organisations today realise the significance of being ethical in their business in order to attract external stakeholders and retain employees. However, majority of the previous studies on CSR mainly focuses on the external stakeholders such as customers, media, investors, and government while the influence of CSR practices from an employee’s perspective (as an internal stakeholder) remains largely undiscovered. The current study investigates university as an entity of organisation to explore their CSR practices. The key focus of this study is on one of the research universities in Malaysia, namely Universiti Putra Malaysia (UPM).